PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA GURU DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING (Studi Kasus pada Sekolah Menengah Kejuruan Negeri 4 Klaten) - Nuryani . (AKTUAL, 2014)
The purpose of this study is investigate influence of leadership, Organization culture, and Organization commitment to teacher performance of the Government Vocational High School 4 at Klaten. The Hypothesizing which have been formulated in this research is: there is direct and indirect influence of leadership, Organization culture across Organization commitment to teacher performance of the Government Vocational High School 4 at Klaten The research is a survey to teacher performance the Government Vocational High School 4 at Klaten with 70 respondent Data have been collected with quesionary was processed with, validity and reliability test, the path analysis, t test, F test and test of R2 The t test have been done show that there is influence of leadership, Organization culture, and Organization commitment to teacher performance the Government Vocational High School 4 at Klaten. The F test have been done show that there is influence of leadership, Organization culture, and Organization commitment to teacher performance the Government Vocational High School 4 at Klaten as simultance. Keyword:leadership,Organization culture, Organization commitment,performance